NVTIA Tomato-Derived Phytomelatonin Produced by Combined Enzymatic Hydrolysis and Extraction: Process Rationale, Stability-Oriented Design, and Translational Evidence - Reed, Damian; Yassine, Jabar; Semenza, Gregg L. (International Journal of Agriculture and Food Sciences Research, 2026)
We evaluated the NVTIA tomato-derived phytomelatonin process as a differentiated natural ingredient platform in the context of contemporary literature on phytomelatonin, tomato biology, melatonin stability, and translational sleep-health evidence. Using the available process-associated dataset, we summarized three optimized production examples and three comparator conditions and then contextualized these findings with peer-reviewed publications on phytomelatonin occurrence in edible plants, tomato melatonin biosynthesis, process-sensitive melatonin degradation, black ginger bioactivity, polyamine biology, and clinical melatonin literature. Across the optimized examples, melatonin content ranged from 98.2% to 99.1%, impurity content remained at or below 1.5%, and microbial limits were reported as compliant. In contrast, comparator conditions without rice germ polyamines or with off-window pH or temperature produced markedly lower melatonin content (82.3%-85.5%) and higher impurity burdens (8.2%-10.5%). Published literature supports the plausibility of a tomato-centered phytomelatonin strategy because tomatoes are recognized edible sources of phytomelatonin and their melatonin biosynthetic route has been mechanistically characterized. The same literature also shows that pH, temperature, light, and storage conditions materially affect melatonin stability, which gives process meaning to the NVTIA emphasis on mild enzymolysis, chromatographic purification, and stabilization. Black ginger and rice germ polyamines provide an additional mechanistic basis for antioxidant and cell-protective positioning, although their direct contribution to finished-product clinical efficacy remains inferential rather than proven. Taken together, the evidence supports NVTIA as a tomato-derived phytomelatonin ingredient with a stability-oriented process design and favorable analytical profile. However, any explicit superiority claim over equivalent commercial materials still requires independent head-to-head analytics, batch reproducibility studies, and controlled human trials.